Sulfur-containing VOCs oxidation catalyst and preparation method and application thereof
The preparation of Cu-based composite oxide catalysts by hydrothermal method solves the problems of high energy consumption, low efficiency and easy catalyst deactivation when removing sulfur-containing VOCs in the prior art, and achieves high-efficiency catalytic oxidation and stability improvement at low temperatures.
Patent Information
- Application Number
- CN202410561085.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The prior art has high energy consumption, low efficiency, operational difficulties and easy catalyst deactivation when removing sulfur-containing VOCs, making it difficult to meet the low-cost, efficient and stable catalytic oxidation needs.
The Cu-based composite oxide catalyst is prepared by mixing titanium salt, cerium salt, zirconium salt and yttrium salt with copper salt, and the Cu-based composite oxide catalyst is prepared by hydrothermal reaction, and the electronic structure of the Cu active site is adjusted by a mixed solution of hydrofluoric acid and sodium fluoride. Lattice oxygen mobility achieves high dispersion and stability of Cu.
Low-temperature and efficient catalytic oxidation of sulfur-containing VOCs is achieved, which significantly improves the stability and sulfur resistance of the catalyst and reduces production costs.
Smart Images

Figure CN118477641B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a sulfur-containing VOCs oxidation catalyst and a preparation method and application thereof. Background Art
[0002] Sulfur-containing volatile organic compounds (sulfur-containing VOCs) are a class of organic chemicals that can cause serious pollution to the atmospheric environment and have high physiological toxicity. They are considered to be one of the important potential precursor pollutants for the formation of photochemical smog and urban smog. Typical sulfur-containing VOCs include methyl mercaptan (CH3SH), methyl sulfide (DMS), methyl disulfide (DMDS), CS2, etc., which are widely present in petroleum refining processes, wood pulp industry, sewage treatment, sanitary landfills and other energy-related activities. Among the existing technologies for removing sulfur-containing VOCs, most methods such as adsorption, regenerative combustion, non-thermal plasma treatment, and biodegradation have problems such as high energy consumption, secondary pollution emissions, low efficiency, and difficult operation. The catalytic oxidation process is considered to be the most promising method for removing sulfur-containing VOCs at present due to its advantages of high purification efficiency, low energy consumption, and few secondary products.
[0003] The key to the catalytic combustion method lies in the design and development of efficient catalysts. The catalyst systems currently widely used for the catalytic oxidation of conventional sulfur-containing VOCs include precious metal catalysts (Pd, Pt, Ru, Au, etc.) and transition metal oxide catalysts (MnO2, Fe2O3, Co3O4, etc.). However, the expensive cost of precious metals restricts their scope of use. At the same time, precious metal catalysts have a strong affinity for sulfur species produced during the catalytic degradation of sulfur-containing VOCs, and are easily deactivated by the deposition and coverage of sulfur species. Transition metal oxide catalysts also react easily with sulfur-containing species to form sulfates due to their active lattice oxygen, which leads to deactivation. Therefore, it is urgent to develop an oxidation catalyst that can efficiently and stably remove sulfur-containing VOCs at a low cost to meet the requirements of protecting human health and reducing air pollution. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a sulfur-containing VOCs oxidation catalyst and a preparation method and application thereof, which has significant low-temperature and sulfur-resistant catalytic effects on the oxidation of sulfur-containing VOCs.
[0005] The technical solution of the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing a sulfur-containing VOCs oxidation catalyst, comprising the following steps:
[0007] S1: stirring and mixing one of a titanium salt precursor, a cerium salt precursor, a zirconium salt precursor and a yttrium salt precursor with a copper salt precursor to obtain a mixed metal salt solution;
[0008] S2: adding a hydrofluoric acid solution or a mixed solution of sodium hydroxide and sodium fluoride dropwise to the mixed metal salt solution obtained in step S1;
[0009] S3: transferring the liquid obtained in step S2 to a hydrothermal reaction kettle for hydrothermal reaction;
[0010] S4: The precipitate obtained after the reaction in step S3 is washed alternately with deionized water and ethanol, and then filtered and calcined to obtain a sulfur-containing VOCs oxidation catalyst.
[0011] The sulfur-containing VOCs oxidation catalyst prepared by the present invention is a composite oxide catalyst, which contains a Cu active phase dispersed at the single atom or sub-nano cluster level, and can significantly adjust the electronic structure and lattice oxygen mobility of the Cu active site. Therefore, the lattice-confined and highly dispersed Cu-based composite oxide catalyst prepared by the present invention can exhibit the advantages of good low-temperature activity and strong stability in the catalytic oxidation purification reaction of sulfur-containing organic waste gas.
[0012] Preferably, in step S1, the titanium salt precursor is n-butyl titanate or isopropyl titanate, and the cerium salt precursor, zirconium salt precursor, yttrium salt precursor and copper salt precursor are nitrate, sulfate or acetate.
[0013] Preferably, in step S1, the molar ratio of the copper salt precursor to the titanium salt precursor, the cerium salt precursor, the zirconium salt precursor or the yttrium salt precursor is 0.01-0.1:1.
[0014] Preferably, in step S2, when the mixed metal salt solution contains a titanium salt precursor, a hydrofluoric acid solution is added dropwise to the mixed metal salt solution, the concentration of the hydrofluoric acid solution is 20-40wt.%, and the volume ratio of the hydrofluoric acid solution to the titanium salt precursor is 0.08-0.16:1; when the mixed metal salt solution contains a cerium salt precursor, a zirconium salt precursor or a yttrium salt precursor, a mixed solution of sodium hydroxide and sodium fluoride is added dropwise to the mixed metal salt solution, wherein the molar ratio of sodium hydroxide to the metal salt in the mixed metal salt solution is 5-15:1, and the molar ratio of sodium fluoride to the metal salt in the mixed metal salt solution is 1-3:1.
[0015] Preferably, in step S3, the temperature of the hydrothermal reaction is 150-200° C., and the hydrothermal reaction time is 12-48 h.
[0016] Preferably, in step S4, the calcination temperature is 300-600° C., and the calcination time is 2-5 hours.
[0017] In a second aspect, the present invention provides a sulfur-containing VOCs oxidation catalyst prepared by the above preparation method.
[0018] Preferably, the sulfur-containing VOCs oxidation catalyst has a mesoporous structure of 5-100 nm and a specific surface area of 40-200 m 2 / g.
[0019] In a third aspect, the present invention also provides the use of the above-mentioned sulfur-containing VOCs oxidation catalyst in the catalytic oxidation reaction of sulfur-containing VOCs.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The sulfur-containing VOCs oxidation catalyst prepared by the present invention uses Cu as an active component and uses inert sulfur-resistant oxides such as Ti, Ce, Zr, and Y as carriers. At the same time, the addition of hydrofluoric acid can confine Cu species in the metal oxide carrier under high-temperature hydrothermal reaction conditions, and the lattice confinement process induced by F ions can improve the dispersion of Cu and weaken the adsorption and deposition of active sites and sulfur species. The lattice-confined high-dispersion Cu-based composite metal oxide can overcome the shortcomings of existing noble metal catalysts, such as high cost, low low-temperature catalytic performance of transition metal oxide catalysts, and easy deactivation by sulfur-containing products, thereby achieving low-temperature, efficient and stable catalytic purification of organic waste gas under specific emission conditions containing sulfur-containing VOCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the XRD spectra of the catalysts prepared in Example 1 and Comparative Examples 1-2.
[0023] Figure 2 It is a catalytic activity curve diagram of the catalysts prepared in Examples 1-2 and Comparative Examples 1 and 3.
[0024] Figure 3 These are the stability evaluation results of the catalysts prepared in Example 1 and Comparative Examples 3-5.
[0025] Figure 4 This is a spherical aberration electron microscope photograph of the catalyst in Example 1. DETAILED DESCRIPTION
[0026] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0028] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0029] Example 1
[0030] This example uses a one-step hydrothermal method to prepare the CuO-TiO2 catalyst, and the specific steps are as follows:
[0031] S1: 25 mL of isopropyl titanate was measured and placed in a beaker. During stirring, copper nitrate particles were added. The molar ratio of copper nitrate to isopropyl titanate was 0.05:1 to obtain a mixed metal salt solution.
[0032] S2 add 3 mL of 20 wt.% hydrofluoric acid solution dropwise to the mixed metal salt solution, and continue stirring after the addition is completed;
[0033] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 hours;
[0034] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a confined copper-titanium composite oxide catalyst, namely, a CuO-TiO2 catalyst.
[0035] Figure 4 This is a spherical aberration electron microscope photograph of the CuO-TiO2 catalyst prepared in this example, proving that the Cu single atoms in the catalyst are confined in the carrier lattice.
[0036] Example 2
[0037] This example uses a one-step hydrothermal method to prepare the CuO-CeO2 catalyst, and the specific steps are as follows:
[0038] S1 Weigh 1.302 g of cerium nitrate and 0.036 g of copper nitrate into 7.5 mL of deionized water and stir until completely dissolved to obtain a mixed metal salt solution;
[0039] S2: weigh 1.44 g of sodium hydroxide and 0.42 g of sodium fluoride, add them to 52.5 mL of deionized water, and stir until completely dissolved to obtain a mixed solution; add the mixed solution dropwise to the mixed metal salt solution of step S1, and precipitate and react for 30 minutes under stirring;
[0040] S3: transferring the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and subjecting it to a hydrothermal reaction at 150°C for 48h;
[0041] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 300° C. for 5 hours to obtain a confined copper-cerium composite oxide catalyst, namely, a CuO-CeO2 catalyst.
[0042] Example 3
[0043] This example uses a one-step hydrothermal method to prepare the CuO-ZrO2 catalyst, and the specific steps are as follows:
[0044] S1 Weigh 1.26 g zirconium nitrate and 0.036 g copper nitrate into 7.5 mL deionized water and stir until completely dissolved to obtain a mixed metal salt solution;
[0045] S2: weigh 1.44 g of sodium hydroxide and 0.42 g of sodium fluoride, add them to 52.5 mL of deionized water, and stir until completely dissolved to obtain a mixed solution; add the mixed solution dropwise to the mixed metal salt solution of step S1, and precipitate and react for 30 minutes under stirring;
[0046] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs a hydrothermal reaction at 200°C for 12 h;
[0047] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 600° C. for 2 hours to obtain a confined copper-zirconium composite oxide catalyst, namely, a CuO-ZrO2 catalyst.
[0048] Example 4
[0049] This example uses a one-step hydrothermal method to prepare the CuO-Y2O3 catalyst, and the specific steps are as follows:
[0050] S1 Weigh 1.29 g of yttrium nitrate and 0.036 g of copper nitrate into 7.5 mL of deionized water and stir until completely dissolved to obtain a mixed metal salt solution;
[0051] S2: weigh 1.44 g of sodium hydroxide and 0.42 g of sodium fluoride, add them to 52.5 mL of deionized water, and stir until completely dissolved to obtain a mixed solution; add the mixed solution dropwise to the mixed metal salt solution of step S1, and precipitate and react for 30 minutes under stirring;
[0052] S3: The obtained liquid is transferred to a polytetrafluoroethylene-lined hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 24h;
[0053] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a confined copper-yttrium composite oxide catalyst, namely, a CuO-Y2O3 catalyst.
[0054] Comparative Example 1
[0055] Comparative Example 1: A single-component nano-sheet TiO2 catalyst was prepared by a hydrothermal method, and the specific steps are as follows:
[0056] S1. Measure 25 mL of isopropyl titanate in a beaker, add 3 mL of 20 wt.% hydrofluoric acid solution dropwise while stirring, and continue stirring after the addition is complete;
[0057] S2 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 h;
[0058] S3 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a single-component nano-sheet TiO2 catalyst.
[0059] Comparative Example 2
[0060] Comparative Example 2 uses an impregnation method to load CuO particles on the TiO2 catalyst prepared in Comparative Example 1. The specific steps are as follows: 0.15 g of copper nitrate trihydrate is dissolved in 2 mL of deionized water, and then the copper nitrate solution is loaded on 1 g of TiO2 catalyst powder prepared in Comparative Example 1 by an equal volume impregnation method. After drying and calcining at 450°C for 4 hours, a CuO / TiO2 catalyst with a Cu loading of 5 mol% is obtained.
[0061] Comparative Example 3
[0062] Comparative Example 3: Nano CeO2 catalyst was prepared by hydrothermal method, and the specific steps are as follows:
[0063] S1 Weigh 1.302 g of cerium nitrate and add it to 7.5 mL of deionized water, stirring until completely dissolved to obtain a mixed metal salt solution;
[0064] S2: Weigh 14.4 g of sodium hydroxide and 4.2 g of sodium fluoride, add them to 52.5 mL of deionized water, and stir until completely dissolved to obtain a mixed solution; add the mixed solution dropwise to the mixed metal salt solution of step S1, and precipitate and react for 30 minutes under stirring;
[0065] S3: The obtained liquid is transferred to a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 100°C for 24h;
[0066] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a nano CeO2 catalyst.
[0067] Comparative Example 4
[0068] Comparative Example 4: The conventional non-sulfur VOCs high-activity MnO2 and Co3O4 catalysts were prepared by coprecipitation method. The specific steps are as follows:
[0069] S1: Dissolve 30 mmol of cobalt nitrate in 100 mL of deionized water to obtain solution A.
[0070] S2 precipitant solution B is 300mL of 0.5mol / L sodium carbonate solution. Solution A and precipitant solution B are simultaneously dripped into a beaker containing 50mL of distilled water, keeping the pH value constant at about 10, and keeping the mixed solution stirred;
[0071] After the addition of S3 is completed, stirring is continued for 2 hours and aging is carried out for 12 hours. The obtained precipitate is filtered and washed with deionized water. The filter cake is dried at 70°C for 12 hours and then dried at 120°C for 12 hours to obtain a precursor material. The precursor material is calcined in air at 450°C for 4 hours to obtain a Co3O4 catalyst.
[0072] Comparative Example 5
[0073] Comparative Example 5 Preparation of Co and Mn lattice confined catalyst CoO by one-step hydrothermal method x -TiO2、MnO x -TiO2, the specific steps are as follows:
[0074] S1: 25 mL of isopropyl titanate is measured and placed in a beaker. Cobalt nitrate or manganese nitrate is added during stirring. The molar ratio of cobalt nitrate or manganese nitrate to isopropyl titanate is 0.05:1 to obtain a mixed metal salt solution.
[0075] S2 add 3 mL of 20 wt.% hydrofluoric acid solution dropwise to the mixed metal salt solution, and continue stirring after the addition is completed;
[0076] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 hours;
[0077] After the hydrothermal reactor is cooled, the precipitate is washed with water and anhydrous ethanol, filtered, dried, and calcined at 450 °C for 4 h to obtain the Co and Mn lattice confined catalyst CoO x -TiO2、MnO x -TiO2.
[0078] Figure 1 It is the XRD spectra of the catalysts prepared in Example 1 and Comparative Examples 1-2. The figure shows that the CuO / TiO2 catalyst prepared in Comparative Example 2 has some XRD diffraction peaks of CuO, while no CuO diffraction peaks are found in the CuO-TiO2 catalyst prepared in Example 1, which indicates that the Cu species in the CuO-TiO2 catalyst prepared in Example 1 exists in a highly dispersed form.
[0079] Comparative Example 6
[0080] Comparative Example 6: A CuO-TiO2-sulfuric acid catalyst was prepared by a one-step hydrothermal method using sulfuric acid hydrolysis. The specific steps are as follows:
[0081] S1: 25 mL of isopropyl titanate was measured and placed in a beaker. During stirring, copper nitrate particles were added. The molar ratio of copper nitrate to isopropyl titanate was 0.05:1 to obtain a mixed metal salt solution.
[0082] S2 add 3 mL of 20 wt.% sulfuric acid solution dropwise to the mixed metal salt solution, and continue stirring after the addition is complete;
[0083] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 hours;
[0084] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a copper-titanium composite oxide catalyst, namely, a CuO-TiO2-sulfuric acid catalyst.
[0085] Comparative Example 7
[0086] Comparative Example 7: A CuO-TiO2-small amount of HF catalyst was prepared by a one-step hydrothermal method, and the specific steps are as follows:
[0087] S1: 25 mL of isopropyl titanate was measured and placed in a beaker. During stirring, copper nitrate particles were added. The molar ratio of copper nitrate to isopropyl titanate was 0.05:1 to obtain a mixed metal salt solution.
[0088] S2 add 1 mL of 20 wt.% hydrofluoric acid solution dropwise to the mixed metal salt solution, and continue stirring after the addition is complete;
[0089] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 hours;
[0090] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a confined copper-titanium composite oxide catalyst, namely, a CuO-TiO2-a small amount of HF catalyst.
[0091] Comparative Example 8
[0092] Comparative Example 8: A Cu-TiO2-small amount of HF catalyst was prepared by a one-step hydrothermal method, and the specific steps are as follows:
[0093] S1: 25 mL of isopropyl titanate was measured and placed in a beaker. During stirring, copper nitrate particles were added. The molar ratio of copper nitrate to isopropyl titanate was 0.05:1 to obtain a mixed metal salt solution.
[0094] S2 add 5 mL of 20 wt.% hydrofluoric acid solution dropwise to the mixed metal salt solution, and continue stirring after the addition is completed;
[0095] S3 transfers the obtained liquid to a polytetrafluoroethylene-lined hydrothermal reactor and performs hydrothermal reaction at 180°C for 36 hours;
[0096] S4 After the hydrothermal reactor is cooled, the obtained precipitate is washed with water and anhydrous ethanol respectively, filtered, dried, and then calcined at 450° C. for 4 hours to obtain a confined copper-titanium composite oxide catalyst, namely, Cu-TiO2-excess HF catalyst.
[0097] Comparative Example 9
[0098] Comparative Example 9: The CuO-MnO2 catalyst was prepared by coprecipitation method, and the specific steps are as follows:
[0099] S1: Dissolve 30 mmol of manganese nitrate and 1.5 mmol of copper nitrate in 100 mL of deionized water to obtain solution A.
[0100] S2 precipitant solution B is 300mL of 0.5mol / L sodium carbonate solution. Solution A and precipitant solution B are simultaneously dripped into a beaker containing 50mL of distilled water, keeping the pH value constant at about 10, and keeping the mixed solution stirred;
[0101] After the addition of S3 is completed, stirring is continued for 2 hours and aging is carried out for 12 hours. The obtained precipitate is filtered and washed with deionized water. The filter cake is dried at 70°C for 12 hours and then dried at 120°C for 12 hours to obtain the precursor material. The precursor material is calcined at 450°C in air for 4 hours to obtain the CuO-MnO2 catalyst.
[0102] Catalyst performance evaluation
[0103] When evaluating the catalytic oxidation performance of sulfur-containing VOCs oxidation catalysts and non-sulfur-containing VOCs oxidation catalysts, a small fixed-bed continuous flow reaction evaluation device was used. The reactants and products were analyzed using an Agilent 7890B gas chromatograph (Agilent), which was equipped with a hydrogen flame ionization detector (FID) for detecting sulfur-containing VOCs (methyl mercaptan, methyl sulfide, ethyl mercaptan, etc.) and non-sulfur-containing VOCs (propane, toluene, etc.), and a thermal conductivity detector (TCD) for detecting CO and CO2. During the test, 100 mg of the catalyst obtained by sieving the tablets with a mesh size of 40-60 was loaded into a quartz tube (inner diameter 6 mm), and the reaction temperature was controlled by a programmed temperature reactor. The reaction gas flow was controlled by a mass flow meter. The reaction gas consisted of 100 ppm sulfur-containing VOCs or non-sulfur-containing VOCs, 10% oxygen and nitrogen balance gas, and was introduced into the catalyst reaction bed at a total flow rate of 50 mL / min, and the space velocity (GHSV) was 30000 mL·g -1 ·h -1Each temperature point was stabilized for at least 30 minutes before sampling and analysis. Stability measurement was performed at 100ppm sulfur-containing VOCs, 10% O2 / N2, total flow rate 50mL / min, GHSV = 30000mL·g -1 ·h -1 , the reaction temperature is 220°C.
[0104] The catalytic oxidation performance evaluation results of the catalysts of Examples 1-4 and Comparative Examples 1-9 are shown in Table 1, where the "catalytic oxidation" referred to in the present invention means that VOCs are mineralized into carbon dioxide and water by oxygen under the action of the catalyst, and no macroscopic flame combustion is shown. When catalytically oxidizing VOCs, the temperature corresponding to the conversion rate of the catalytic oxidation of the target VOCs is 50%, which is called the "ignition temperature" and is recorded as T 50 The temperature corresponding to the conversion rate of the target VOCs catalytic oxidation of 90% is called the "complete conversion temperature" and is recorded as T 90 .
[0105] Table 1 Evaluation results of water-gas shift activity on different catalysts under different conditions
[0106]
[0107]
[0108] As shown in Table 1, compared with Examples 1-4, the methyl mercaptan conversion temperature of the catalysts of Comparative Examples 1-3 is increased, which can be attributed to the improved catalytic performance caused by the lattice confinement of the Cu species in the catalysts of Examples 1-4. Compared with Example 1, the propane conversion temperature of the catalyst of Comparative Example 4 is reduced, but Figure 3 It can be seen that the methyl mercaptan oxidation stability of the catalyst of comparative example 4 is poor, indicating that conventional non-sulfur-containing VOCs catalysts are not suitable for the catalytic oxidation of sulfur-containing VOCs such as methyl mercaptan. Compared with Example 1, the methyl mercaptan conversion temperature of the catalyst of comparative example 5 increases, which shows that only the catalyst confined by Cu species has methyl mercaptan low-temperature activity, while the catalyst confined by species such as Co and Mn cannot achieve this effect. Compared with Example 1, the methyl mercaptan conversion temperature of the catalyst of comparative examples 6-8 increases, indicating that the presence and content of F ions in the catalyst synthesis process play an important role in the generation of highly active confined Cu species. Compared with Examples 1-4, the methyl mercaptan conversion temperature of the catalyst of comparative example 9 increases, indicating that the carrier selection of confined Cu species also has an impact on the performance of the catalyst, and when the carrier is an oxide of Ti, Ce, Zr or Y, the performance of the prepared catalyst is better.
[0109] Figure 2It is a catalytic activity curve diagram of the catalysts prepared in Examples 1-2 and Comparative Examples 1 and 3. It can be seen from the figure that the activity of the catalyst containing confined Cu species in Examples 1-2 is much better than that of the catalyst not containing Cu species in Comparative Examples 1 and 3.
[0110] Figure 3 These are the stability evaluation results of the catalysts prepared in Example 1 and Comparative Examples 3-5, which illustrate that the Cu species-confined CuO-TiO2 catalyst prepared in Example 1 has significant stability advantages over other species-confined or non-sulfur-containing VOCs catalysts.
Claims
1. A method for preparing a sulfur-containing VOCs oxidation catalyst, characterized in that: The following steps are involved: S1: stirring and mixing one of a cerium salt precursor, a zirconium salt precursor and a yttrium salt precursor with a copper salt precursor to obtain a mixed metal salt solution; S2: adding a mixed solution of sodium hydroxide and sodium fluoride dropwise to the mixed metal salt solution obtained in step S1; S3: transferring the liquid obtained in step S2 to a hydrothermal reaction kettle for hydrothermal reaction; S4: washing the precipitate obtained after the reaction in step S3 with deionized water and ethanol alternately, filtering and calcining to obtain a sulfur-containing VOCs oxidation catalyst; In step S2, the molar ratio of sodium hydroxide to the metal salt in the mixed metal salt solution is 5-15:1, and the molar ratio of sodium fluoride to the metal salt in the mixed metal salt solution is 1-3:
1.
2. The method for preparing a sulfur-containing VOCs oxidation catalyst according to claim 1, characterized in that: In step S1, the cerium salt precursor, the zirconium salt precursor, the yttrium salt precursor and the copper salt precursor are nitrate, sulfate or acetate.
3. The method for preparing a sulfur-containing VOCs oxidation catalyst according to claim 1, characterized in that: In step S1, the molar ratio of the copper salt precursor to the cerium salt precursor, the zirconium salt precursor or the yttrium salt precursor is 0.01-0.1:
1.
4. The method for preparing a sulfur-containing VOCs oxidation catalyst according to claim 1, characterized in that: In step S3, the temperature of the hydrothermal reaction is 150-200° C., and the hydrothermal reaction time is 12-48 hours.
5. The method for preparing a sulfur-containing VOCs oxidation catalyst according to claim 1, characterized in that: In step S4, the calcination temperature is 300-600° C., and the calcination time is 2-5 hours.
6. A sulfur-containing VOCs oxidation catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. The sulfur-containing VOCs oxidation catalyst according to claim 6, characterized in that: The sulfur-containing VOCs oxidation catalyst has a mesoporous structure of 5-100nm and a specific surface area of 40-200m 2 / g.
8. Use of the sulfur-containing VOCs oxidation catalyst as claimed in claim 6 in the catalytic oxidation reaction of sulfur-containing VOCs.
Citation Information
Patent Citations
Composite oxide catalyst for synchronously removing VOCs (Volatile Organic Compounds) and NOx in sulfur-containing flue gas as well as preparation method and application of composite oxide catalyst
CN114160147A